Chloridomethylphenyl(quinoline-2-carboxylato-kappa 2 N,O)tin(IV) - Vafaee, M.; Amini, M.M.; Ng, S.W. (International Union of Crystallography, 2010)
The Sn atom in the title compound, [Sn(CH(3))(C(6)H(5))(C(10)H(6)NO(2))Cl], shows a distorted C(2)SnNOCl trigonal-bipyramidal coordination; the apical sites are occupied by the N and Cl atoms